Merger Policy and Tax Competition - Andreas Haufler; Christian Schulte (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
In many situations governments have sector-specific tax and regulation poli- cies at their disposal to in°uence the market outcome after a national or an international merger has taken place. In this paper we study the implications for merger policy when countries non-cooperatively deploy production-based taxes. We find that whether national or international mergers are more likely to be en- acted in the presence of nationally optimal tax policies depends crucially on the ownership structure of firms. When all firms are owned domestically in the pre- merger situation, non-cooperative tax policies are more efficient in the national merger case and smaller synergy effects are needed for this type of merger to be proposed and cleared. These results are reversed when there is a high degree of foreign firm ownership prior to the merger.
Keywords: H21; H77; L13; L50; 330; merger regulation; tax competition